بەشاریبوون وگەشەى شارنشینى لە دەوڵەتى پێشكەوتوودا - مصطفى, عالیە فرج; محمد, نیاز عزالدین (Sulaimani Journal for Humanities, 2021)
Urbanization in developed countries: Urbanization is considered one of the sustainable and driving factors for change in various areas of society, in addition to the fact that urbanization as a demographic, social and development process in turn affects the patterns of urban behavior. Urbanization is one of the processes of different dimensions that differ between developed countries and different countries in terms of their dependence in the developed countries on: the presence and presence of elite technicians and specialists, the change in population density, the continuous change in the hierarchy of industrial and commercial professions, the presence of urban planning.... etc. The role and impact of urbanization in developed countries is manifested in: the continuation of the development of professional specializations into more precise specializations, the opportunity available to citizens for political participation and influence in political decision-making processes, different types of transition opportunities to life levels. In this study, the researcher relied on the historical approach and the descriptive and analytical method to study both urbanization and urban growth in developed countries, as well as taking into account the difference of societies in an attempt to reveal the factors and indicators related to urbanization and urban growth.